Viendas a la orilla del rio - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Vivienda rural construidos con materiales de la zona al borde del rio
ENGLISH: Rural housing built with local materials at the river's edge

SPANISH: Vivienda rural construidos con materiales de la zona al borde del rio
ENGLISH: Rural housing built with local materials at the river's edge
Houses on the riverbank
Keywords: Iquitos (Perú)|~|Rural|~|Houses|~|Vivienda rural|~|río Itaya|~|